Boards that excel : candid insights and practical advice for directors - White, B. Joseph (BK business book., 2014)
"Having served on numerous corporate and nonprofit boards, former business school dean and university president White has a surprising message--many directors don't understand their roles as stewards. Rather than seeing boards as mere vehicles for oversight and basic monitoring, he shows, in detail and with hundreds of real-world anecdotes, how boards can do better"--